2011
DOI: 10.1007/s00253-011-3618-3
|View full text |Cite
|
Sign up to set email alerts
|

The actinobacterium Microbacterium sp. 16SH accepts pBBR1-based pPROBE vectors, forms biofilms, invades roots, and fixes N2 associated with micropropagated sugarcane plants

Abstract: Members of the genus Microbacterium lineage of Gram-positive actinobacteria are increasingly being reported to display significant traits associated with environmental biotechnology and bioengineering. 16SH is a nitrogen-fixing bacterial strain isolated from a surface-sterilized stem of sugarcane grown in Guangxi, China. Analysis of 16S rRNA gene sequences revealed that 16SH belonged to the genus Microbacterium. pPROBE-pTet(r) plasmids were constructed by cloning the promoter region of the Tet(r) gene into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 47 publications
2
44
0
Order By: Relevance
“…PCR amplifications of the internal transcribed spacer region (ITS) and translation elongation factor (TEF) were performed with the primers ITS1/ITS4 [24] and ef1/ef2 [25]. The respective amplification products of 550 bp and 650 bp were purified, cloned and sequenced as previously described [26]. The obtained putative ITS and TEF sequences of the fungal isolate SaCS12 were BLASTed [27] and deposited in the GenBank database under JQ039192 and JQ039193, respectively.…”
Section: Fungal Identificationmentioning
confidence: 99%
“…PCR amplifications of the internal transcribed spacer region (ITS) and translation elongation factor (TEF) were performed with the primers ITS1/ITS4 [24] and ef1/ef2 [25]. The respective amplification products of 550 bp and 650 bp were purified, cloned and sequenced as previously described [26]. The obtained putative ITS and TEF sequences of the fungal isolate SaCS12 were BLASTed [27] and deposited in the GenBank database under JQ039192 and JQ039193, respectively.…”
Section: Fungal Identificationmentioning
confidence: 99%
“…At present, little is known about the diversity and predominant population of nitrogen-fixing bacteria associated with the sugarcane plants growing in Guangxi. Recently, some nitrogen-fixing bacteria have been isolated from sugarcane plants grown in Guangxi (26, 28, 44, 52, 53) using NFb, JNFb and LGI-P media that were respectively used to isolate Azospirillum (10), Herbaspirillum (6) and Gluconacetobacter diazotrophicus (8); however, nitrogen-fixing bacteria belonging to the genera Azospirillum , Herbaspirillum , and Gluconacetobacter , which are predominantly associated with sugarcane plants in Brazil, have not been isolated. The diversity of nitrogen-fixing bacteria associated with sugarcane plants grown with high N-fertilization in Guangxi may be different from in Brazil.…”
mentioning
confidence: 99%
“…The recommended dose of urea fertilization for plant cane crops at the seedling stage is 180 kg ha −1 , 30% of urea fertilization for a season (46). Recent studies have shown that nitrogen-fixing bacterial strains isolated from other sugarcane cultivars are able to provide nitrogen to micropropagated ROC22 sugarcane seedlings via BNF and promote sugarcane growth (26, 29); however, neither indigenous nitrogen-fixing bacteria associated with ROC22 sugarcane plants nor their associative BNF under recommended N-fertilization have been investigated.…”
mentioning
confidence: 99%
“…Many Microbacterium spp. play a significant role in oil, lactone and xylan degradation, production of biosurfactants, and as a growth promoter in plants (Lin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%